Review of Systematic Reviews on Acute Procedural Pain in Children in the Hospital Setting - Jennifer Stinson; Janet Yamada; Alison Dickson; Jasmine Lamba; Bonnie Stevens (Pain Research and Management)
BACKGROUND: Acute pain is a common experience for hospitalized children. Despite mounting research on treatments for acute procedure-related pain, it remains inadequately treated.